Father absence and psychological well-being among Indonesian migrant children in Malaysia: Protective roles of community learning centers and religious education - Ilfiatul Marhamah; Iwan Kuswandi; M Ridwan; Wong Su Lee (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2026)
Paternal migration in Indonesian migrant-worker families presents a social paradox: improved household economic security coincides with reduced paternal emotional presence, or father absence, which may adversely affect children’s psychological well-being. This study examines the effect of father absence on the psychological well-being of primary-school-aged Indonesian migrant children in Malaysia, studies the mediating roles of Community Learning Centers (Sanggar Bimbingan) and religious education, and explores the psychosocial mechanisms that support children’s psychological robustness. A sequential explanatory mixed-methods design was used. Quantitative data were collected using Ryff’s Psychological Well-Being Scale and the Strengths and Difficulties Questionnaire (SDQ) and analyzed by regression and mediation analyses. Qualitative data were obtained through interviews and examined using Reflexive Thematic Analysis. The results show that father absence negatively affects children’s psychological well-being, whereas Community Learning Centers and religious education serve as protective factors by providing psychosocial and spiritual support. The qualitative findings further demonstrate that teachers, peers, and religious activities help improve migrant children's emotional management, optimism, learning motivation, and psychological resilience. The study determines that the adverse effects of father absence can be mitigated through supportive educational and religious environments. Accordingly, stronger collaboration among the Embassy of the Republic of Indonesia, Community Learning Centers, schools, religious organizations, and government agencies is required to develop sustainable educational services and psychosocial support for Indonesian migrant children.